2008
DOI: 10.1002/macp.200800063
|View full text |Cite
|
Sign up to set email alerts
|

An H‐Bonded Main‐Chain Liquid‐Crystalline Polymer Obtained by In Situ Photochemical Conversion from an H‐Bonded LC Dimer

Abstract: An H‐bonded main‐chain liquid‐crystalline (LC) polymer was obtained by in situ photochemical conversion from an H‐bonded LC dimer. A bifunctional compound, 1, having a cinnamoyl group at one end and a carboxylic acid group at the other, was synthesized as the H‐bonded LC dimer. UV irradiation of 1 in the LC phase in the presence of a sensitizer resulted in its conversion to a photodimer, with a carboxylic acid at both ends, through photocycloaddition of the cinnamoyl moiety. The LC phase was maintained during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…A decrease in the trans ‐vinylene C‐H out‐of‐plane deformation (Figure S4) is diagnostic of a [2+2] cycloaddition reaction of the alkene 15. 19 This indicated that 2‐NA formed a cyclobutane structure in the gel. Meanwhile, the appearance of a bending vibration of the saturated C‐H of the cyclobutane at $\tilde \nu $ =1441 cm −1 in the spectrum of the 2‐NA precipitate (Figure S5) verified the topochemical reaction 20.…”
Section: Resultsmentioning
confidence: 94%
“…A decrease in the trans ‐vinylene C‐H out‐of‐plane deformation (Figure S4) is diagnostic of a [2+2] cycloaddition reaction of the alkene 15. 19 This indicated that 2‐NA formed a cyclobutane structure in the gel. Meanwhile, the appearance of a bending vibration of the saturated C‐H of the cyclobutane at $\tilde \nu $ =1441 cm −1 in the spectrum of the 2‐NA precipitate (Figure S5) verified the topochemical reaction 20.…”
Section: Resultsmentioning
confidence: 94%
“…Moreover, the intensities of the vinylene C]C stretching vibration band at 1636 cm À1 is significantly lowered, and the ]C-H stretching and deformation vibration bands at 3040 cm À1 and 970 cm À1 disappear after 4 h irradiation. [36][37][38][39][40][41][42] These are powerful proofs for the loss of the vinylene C]C bond due to photodimerization. Meanwhile, the appearance of the stretching and bending vibration of saturated C-H of the cyclobutane at 2899 and 1343 cm À1 , 37 respectively, after UV irradiation, unambiguously confirms the occurrence of the photodimerization in the tubular membranes formed by SHHC molecules.…”
Section: Resultsmentioning
confidence: 99%